Economic Misery, Ecological Unsustainability, and the Remedial Responsibility of the Global Affluent - Yukinori Iwaki (Global justice: Theory, Practice, Rhetoric)
The global affluent are contributing to and benefiting from the systemic cause of economic misery and ecological unsustainability. Some philosophers have invoked this relational point to discuss the responsibility of the affluent because by doing so, they assume, one can formulate a more compelling argument than non-relational arguments. This paper supports this relational strand by drawing upon David Miller’s theory of ‘remedial responsibility.’ Although Miller himself seems to deny the said relational point, this paper shall defend it based upon critical economic studies. The first section summarises Miller’s non-relational argument. The second section assesses it, and in the process develops what can be described as a ‘relational remedial theory of global justice.’ The third section discusses a few significant problems that this theory would encounter. Specifically, it argues that the establishment of a ‘cosmopolitan democracy,’ which would facilitate dialogues among global citizens, may serve to overcome those problems.